Scc2 counteracts a Wapl-independent mechanism that releases cohesin from chromosomes during G1 - Srinivasan, M; Petela, NJ; Scheinost, JC; Collier, J; Brunet, M; Roig, MB; Beckouët, F; Hu, B; Nasmyth, KA (eLife Science Publications, 2019)
Cohesin’s association with chromosomes is determined by loading dependent on the Scc2/4 complex and release due to Wapl. We show here that Scc2 also actively maintains cohesin on chromosomes during G1 in S. cerevisiae cells. It does so by blocking a Wapl-independent release reaction that requires opening the cohesin ring at its Smc3/Scc1 interface as well as the D loop of Smc1’s ATPase. The Wapl-independent release mechanism is switched off as cells activate Cdk1 and enter G2/M and cannot be turned back on without cohesin’s dissociation from chromosomes. The latter phenomenon enabled us to show that in the absence of release mechanisms, cohesin rings that have already captured DNA in a Scc2-dependent manner before replication no longer require Scc2 to capture sister DNAs during S phase.